“It’s not my job to teach writing”: Activity theory analysis of [invisible] writing practices in the engineering curriculum practices in the engineering curriculum - Goldsmith, Rosalie; Willey, Keith (Journal of Academic Language and Learning, 2016)
Although writing is still the main form of assessment at university, the practice of writing continues to be marginalised, particularly in technical disciplines such as engineering, notwithstanding decades of reports identifying gaps in graduate communication abilities in these fields, and diverse interventions to address these gaps. The assumption underlying many of the reports and interventions is that engineering students neither value nor are interested in writing, but actually many engineering students are not provided with the opportunity to develop or practise disciplinary writing in the subjects they study, despite being required to write in a range of genres as part of their assessment. This implies that writing practices are neither seen as developmental nor as intrinsic to the engineering curriculum. This demands the question: why not? This paper reports on a study investigating perceptions of writing practices in the engineering curriculum at the level of engineering academics. Using activity theory to capture the dynamic interactions of the various participants in engineering subjects, the study analyses the perspectives of engineering subject coordinators about writing practices in their subjects through interviews and documents. Current findings show tensions between the value of propositional or technical knowledge and that of writing practices. These findings can be used to develop a discussion with engineering academics to emphasise the developmental nature of writing and to make writing practices more visible in the engineering curriculum.